The Role of the ILO in Resolving Violence Against Indonesian Crew on Fishing Vessels - Yordan Gunawan; Andi Pramudya Syamsu (Fiat Justisia, 2023)
In response to alarming reports of forced labor among seafarers on fishing boats globally, the International Labor Organization (ILO) established ILO Convention No. 188 in 2007, which sets essential regulations for ensuring safety and protecting crew members from exploitation and injury within the fishing industry. This protection is particularly vital due to instances of violence against Indonesian workers on fishing vessels owned by Chinese and Taiwanese companies, which have tragically resulted in numerous fatalities among Indonesian crew members. This research aims to examine the roles of the ILO and the Government of Indonesia, as the country of origin for many fishing vessel crews, in addressing the violence faced by these workers. Utilizing qualitative research methods, the study gathers information from a variety of relevant sources, including conventions, academic journals, legal texts, and other literature pertinent to the issue. Despite Indonesia having laws that protect migrant workers and having ratified ILO Convention 111 concerning discrimination in employment and occupation, these measures fall short in effectively addressing the problem. Consequently, the ILO's active collaboration with countries worldwide is urgently needed to tackle this global issue and to encourage member states, particularly Indonesia—home to a significant population of fishermen and crew members on foreign vessels—to ratify ILO Convention 188.